Types of middle voice in Indonesian language (Tipe-tipe diatesis medial dalam Bahasa Indonesia) - I Nyoman Kardana (Fakulti Sains Sosial dan Kemanusiaan, 2011)
As the national language, Indonesian language has been often used as the object of linguistic study conducted by both local and foreign linguists. In this case, this study is concerned with the types and morphological structure of verbs in Indonesian middle voice. Data was gained through interview method to some speakers of Indonesian. The data was completed by those taken from daily newspaper Bali Post. Based on the analysis it was found that the middle voice in Indonesian can be distinguished into lexical, morphological, and periphrastic middle. Lexical middle is only constructed by zero intransitive verbs and the action conducted by ACTOR refers back to the ACTOR. Morphological middle results from affixes (ber-) and (ber-/-an) attached to verb and noun bases. Periphrastic middle is possibly derived from morphological middle. Affixes commonly used to produce periphrastic middle are transitive affixes (meN-), (meN-/-kan), and (meN-/-i) with their various forms depending on the initial phoneme of the bases. Semantically, middle voice in Indonesian Language is classified into ten types in accordance with what is proposed by Kemmer, they are (1) grooming or body action middle, (2) change in body posture middle, (3) non-translational motion middle, (4) translation motion middle, (5) indirect middle, (6) emotion middle, (7) cognitive middle, (8) spontaneous middle, (9) reciprocal situation middle, and (10) middle of action of emotion.